Best Super Bowl quarterbacks - Bowker, Paul, 1954- (Bowker, Paul, 1954- Best of the Super Bowl., 2019)
Profiles twelve of the best quarterbacks to ever play in an NFL Super Bowl including Peyton Manning, Tom Brady, and Joe Namath. Includes photographs, facts and stories, a glossary, and sources for further learning.